Cities as parasitic amplifiers? Malaria prevalence and diversity in great tits along an urbanization gradient - Caizergues, Aude E.; Robira, Benjamin; Perrier, Charles; Jeanneau, Mélanie; Berthomieu, Arnaud; Perret, Samuel; Gandon, Sylvain; Charmantier, Anne (Peer Community Journal)

(untitled)
Urbanization is a worldwide phenomenon that modifies the environment. By affecting the reservoirs of pathogens and the body and immune conditions of hosts, urbanization alters the epidemiological dynamics and diversity of diseases. Cities could act as areas of pathogen dilution or amplification, depending on whether urban features have positive or negative effects on vectors and hosts. In this study, we focused on a host species and investigated the prevalence and diversity of avian malaria parasites (Plasmodium/Haemoproteus sp. and Leucocytozoon sp.) in great tits (Parus major) living across an urbanization gradient. In general, we observed high prevalence in adult birds (from 95% to 100%), yet lower prevalence in fledglings (from 0% to 38%). We found a slight tendency for increased Plasmodium sp. prevalence with increasing urbanization in adults. Urban nestlings had higher Plasmodium sp. infection rates than non-urban nestlings. We found evidence of higher diversity of parasites in the most natural urban park; however, parasite diversity was similar across other urbanization levels (e.g. from a little artificialized park to a highly anthropized industrial area). Parasite lineages were not habitat specific. Only one Plasmodium sp. lineage (YWT4) was associated with urban areas and some rare lineages (e.g., AFR065) were present only in a zoo area, perhaps because of the presence of African birds. This study suggests that urbanization can lead to a parasite amplification effect and can favor different avian malaria lineages.